Trade-offs involved in the choice of cloud service configurations when building secure, scalable, and efficient Internet-of-Things networks. (February 2020) - Mishra, Amitabh; Reichherzer, Thomas; Kalaimannan, Ezhil; Wilde, Norman; Ramirez, Ruben
This article focuses on results obtained from two cloud-based models that examine trade-offs between security, scalability, and efficiency of data collection for Internet-of-Things sensor networks. This work can provide insight for Internet-of-Things systems designers in choosing security controls and scalability features when working with cloud services. The results were obtained from a smart home Internet-of-Things prototype system in which data records from in-home sensors are transmitted wirelessly to an in-home hub, which forwards them to a cloud web service for storage and analysis. We consider different configurations and security controls on the wireless (in-home) and on the wired (home-to-web) sides. The configuration on the wireless side includes encrypted or plain-text transmission from the wireless sensors to the in-home hub for probing if software encryption of sensor data adds appreciable delay to the transmission time. The configuration on the wired side includes encryption or plain-text transmission, with or without authentication, with or without scalable cloud services. For each configuration, we measure end-to-end latency, transmission latency, and processing latency at the web service. Results of the experiments on the wired side showed much greater latencies and variability of latencies when using scalable cloud services.